ANALISIS PERUBAHAN TUTUPAN LAHAN DI AREAL KONSESI IUPHHK-HA PT BINTANG LIMA MAKMUR KABUPATEN MALUKU TENGAH - Ellen Papilaya; Ronny Loppies; Aryanto Boreel (JURNAL HUTAN PULAU-PULAU KECIL, 2023)
This study aims to analyze land cover in the concession area of IUPHHK-Ha PT. Bintang Lima Makmur, Analyzing land cover changes in the IUPHHK-Ha concession area of PT. BLM 2010-2020, and Identifying the factors causing land cover changes in the IUPHHK-Ha concession area of PT. BLM. This research uses Landsat 7 ETM satellite imagery in 2010 and Landsat 8 OLI in 2015, 2020 (Path 108, Row 62). Downloaded directly from the United States Geological Survey (USGS) website (https://glovis.usgs.gov/). This study uses a guided classification, the results of land cover classification in 2010, 2015, and 2020 consisting of primary dry land forest, secondary dry land forest, shrubs, dry land mixed bush agriculture, open land, and bodies of water, from 2010 to 2020 the land cover class that experienced the largest change was secondary dryland forest at 25.25%, and the smallest was water bodies at 0.10%, and factors that influence land cover changes, namely; production activities of PT. BLM and also the livelihoods of local residents